1986
DOI: 10.1007/bf01402394
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the glial fibrillary acidic protein in human cerebrospinal fluid and in cyst fluid of brain tumors

Abstract: The glial fibrillary acidic protein (GFAP) have been quantitatively determined in over 200 samples of liquid content of brain tumours and in cerebrospinal fluid (CSF) of cases with various tumours of the cerebral nervous system. For establishing the GFAP value, the rocket radioimmunoelectrophoresis was used. The studies were performed in three series of patients. The GFAP value of fluids from 26 cysts of both neoplastic and non-neoplastic type had a wide range of 0.6 microgram/ml to 40 micrograms/ml. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…This is the case for GFAP (peak at 49 916 Da, Table 1 ) and for VEGF121 (peak at 17 224 Da, Table 2 ). 1, 12 …”
Section: Resultsmentioning
confidence: 99%
“…This is the case for GFAP (peak at 49 916 Da, Table 1 ) and for VEGF121 (peak at 17 224 Da, Table 2 ). 1, 12 …”
Section: Resultsmentioning
confidence: 99%
“…GFAP, glial fibrillary acidic protein, is an intermediate filament (IF) protein which works as a holder of astrocyte mechanical strength. It is a well-known marker for astrocytes [ 74 ]. It has been reported that cells with astrocytic property can serve as an origination of new neurons during adult neurogenesis [ 75 ].…”
Section: Molecular Biomarkers During Adult Neurogenesismentioning
confidence: 99%
“…An early study has found CSF GFAP levels to be higher in glioblastoma than in other brain tumors and to be persistently elevated following incomplete tumor resection (Szymaś et al., 1986). Elevated CSF GFAP levels have also been associated with dementia (Ishiki et al., 2016), Alexander Disease (Jany et al., 2015) and multiple sclerosis (Kassubek et al., 2017).…”
Section: Discussionmentioning
confidence: 99%